Supporting Movement Equipment for Learning Basic Locomotor and Manipulative Movements for Students with Special Needs for visual impairment - Mashudhi, Mardhani Putra; Sulaiman, Sulaiman; Soegiyanto, Soegiyanto (Journal of Physical Education and Sports, 2021)
The background of this research is that with the development in education, the limited infrastructure in special schools will affect the learning process of physical education. Utilizing tools that can be used in learning and modifying games with the true goal of Physical Education Sport and health,namely how to make students move, feel happy and sweat when learning physical education place. This tool consists of basic movements of walking, running, and jumping.The purpose of this research is to produce motion aid products that can make it easier for teachers and students to perform locomotor movements, test the effectiveness of students' use of mobility aids in the movement learning process.. This research is a type of development research. Research development (R&D) is the process used to develop and validate educational products. The instruments used in this study include (1) an assessment sheet/questionnaire; (2) research subjects,Data analysis Likert scale is changing the assessment in the form of qualitative to quantitative. This research has produced a mobility aid product withproduct trial results on a small scale with an average rating score of 4.56 or 91.20% and product trials on a large scale with an average rating score of 4.525 or 90.50%. The conclusions of the research and discussion resulted in a product of Locomotor and Manipulative learning motion aids for the visually impaired which can facilitate students. Suggestions for product development of motion aids for the blind are recommended to adaptive physical education teacher to be used as a tool in learning.